Quality in the calculation of the Burden (B) based in the mathematical model of López Jimeno to contribute in the management of the risk in the blasting, in quarry of limestone rock - Peña Castillo, Manuel F. (2019)
The objective of the present work is to contribute in calculating approximately the best perpendicular distance from the center of the drill (cylindrical hole) of production to the nearest free face called Burden (B), being the most important factor in the design of the blasting in the Merced quarry, to optimize the fragment size at 35 c.m. required and contribute in the management of the risks in the blasting of the quarry. For this, tests have been carried out in the different limestone rock blasts in the quarry called the Merced located in the district of Chilca - Lima, where it was determined that the best mathematical model for the calculation of the burden is that of López Jimeno (1980) for drills with 1,5-inch diameter perforations and with a drilling length of 8 feet; where the intervening variables are: diameter of the drill, the density of the rock, seismic velocity of the rock, density of the explosive confined in the drill and the speed of detonation of the explosive. The collection of qualitative and quantitative data in information, based on the trial and error technique for the calculation of the most optimal Burden (B) accompanied by an adequate design of the perforation mesh, the characteristics and conditions of the rock were evaluated to evaluate later the results of the blasting.